The probabilistic logic of communication and change. (7th January 2016) - Achimescu, Andreea; Baltag, Alexandru; Sack, Joshua
Abstract: This article introduces a Probabilistic Logic of Communication and Change, which captures in a unified framework subjective probability, arbitrary levels of mutual knowledge and a mechanism for multi-agent Bayesian updates that can model complex social-epistemic scenarios, such as informational cascades. We show soundness, completeness and decidability of our logic, and apply it to a concrete example of cascade.